Combining the Best of Two Worlds: Nanoparticles and Nanofibers. Issue 8 (8th July 2014) - Bannwarth, Markus; Crespy, Daniel
Abstract The preparation and applications of nanoparticles and nanofibers are widely described in the literature. Both types of materials have specific advantages but also drawbacks. We discuss here the methods to fabricate nanofibers from nanoparticles and vice versa by template‐free methods and colloid‐electrospinning. Nanoparticles and nanofibers can be also synergistically combined to yield nanostructured constructs that display highly advantageous properties such as good mechanical integrity, double protection of encapsulated substances, or the possibility to co‐encapsulate payloads with different polarities.